Analyzing resilience in small and medium-sized enterprises: A fuzzy cognitive mapping-based approach - Joana M.P. Branco; Major, M.; Meidute-Kavaliauskiene, I.; Banaitis, A.; Falcão, P. F. (Proceedings of the 2019 International Conference on Management and Education (MAE 2019), 2019)
Resilience is an increasingly important concept in current socioeconomic landscapes. Due to the competitive global context in which we live, this trend is particularly noticeable in small and medium-sized enterprises (SMEs). Due to their limited resources and capabilities, these firms are exposed to unfavorable scenarios that can threaten their stability, viability, and development (i.e., their resilience). Thus, identifying the determinants of SME resilience and their respective cause-and-effect relationships is a vital endeavor because these companies’ resilience involves a wide variety of conceptual or theoretical issues that need to be understood more fully. This study proposes the creation of a fuzzy cognitive map (FCM) as a novel way to analyze the determinants of SME resilience. The FCM was developed based on the insights obtained during two intensive group meetings with a panel of SME managers and entrepreneurs. The resulting well-informed, process-oriented framework contains the determinants that need be considered in this research context. The static and dynamic analyses carried out produced an improved understanding of the cause-and-effect relationships between determinants of SME resilience, which facilitates better strategic planning by these firms’ managers. The practical implications, advantages, and limitations of the proposed approach are also discussed.